Міграційна криза в ЄС: проблема безпеки зовнішніх кордонів та загострення міжетнічних - Луцишин, Галина (Lviv Politechnic Publіshing House, 2015)
Розглянуто проблему сучасної міграційної кризи в країнах ЄС, основні загрози безпеці зовнішніх кордонів ЄС та загострення міжетнічних конфліктів. Проаналізовано сучасну міграційну політику країн ЄС, проблеми інтеграції мігрантів у європейські суспільства, заходи, які застосовують окремі європейські держави у боротьбі із нелегальною міграцією, а також наголошено на необхідності вдосконалення сучасної міграційної політики країн ЄС, розробки нових умов та принципів адаптації мігрантів. This article covers the problem of the current migration crisis in the EU countries. Special focus is placed on analyzing problems with the security of EU external borders and aggravating inter-ethnic conflicts. The author notes that the migration wave brings along the problem of the integration of migrants in European societies, revives the ethnocentric rhetoric of many European politicians. Further, the theory of multiculturalism is criticized, anti-Islamic sentiment is intensifying, ultra-right and nationalist parties are developing in European countries. Issues such as the protection of EU external borders, a fair allocation of refugees who are already in the European territory among EU countries are especially topical for the EU because today Hungary and Croatia can no longer manage the great numbers of refugees who have crossed their borders. Steps taken by individual European countries against illegal migration, including the decision of the Hungarian government to engage the military in holding back migrants, fail to solve the problem. Liability introduced for refugees crossing the border illegally has low effectiveness. The current situation commands an overhaul of the existing migration policy of EU countries, the development of new conditions and principles of the adaptation of immigrants. Of course, critical elements of the institutionalization of migrants include their national and network organizations. Their Diaspora has a special influence on the integration of migrants in host societies. The objective of the integration of immigrants, which is of top priority for Europeans, is unlikely to involve meaningful concessions for them. Continued tough focus on immigration policy in terms of both individual states. and the overall European Union will only strengthen the antagonism between migrants and native Europeans.
Migration crisis in the EU: security of external borders at stake and inter-ethnic relationships aggravating
Keywords: міграція; Європейський Союз; національна безпека; інтеграція мігрантів; етнополітичні конфлікти; мультикультуралізм; migration; the European Union; national security; integration of migrants; ethnic and political conflicts; multiculturalism